The effects of red LED light on pig sperm function rely upon mitochondrial electron chain activity rather than on a PKC-mediated mechanism - Blanco-Prieto, Olga; Maside, Carolina; Àlex Peña,; Ibáñez-Príncep, Júlia; Bonet, Sergi; Yeste, Marc; Rodríguez-Gil, Joan E. (Frontiers in Cell and Developmental Biology, 2022)
While irradiation with red LED light has been reported to modulate sperm function in different mammalian species, the mechanisms underlying their response are poorly understood. This work sought to provide new insights into whether this effect relies on a direct action upon mitochondrial electron chain and/or on PKC-linked mechanisms such as those related to opsins. For this purpose, pig semen was light-stimulated for 1 min, 5 min or 10 min in the presence/absence of antimycin A, an inhibitor of the mitochondrial electron chain, or PKC 20-28® (PKCi), a PKC inhibitor. Antimycin A completely blocked the effects of light at all the performed irradiation patterns. This effect was linked to a complete immobility of sperm, which was accompanied with a significant (P<0.05) drop in several markers of mitochondrial activity, such as JC-1 staining and O2 consumption rate. Antimycin A, however, did not affect intracellular ATP levels, intramitochondrial calcium, total ROS, superoxides or cytochrome C oxidase (CCO) activity. In the case of PKCi, it did also counteract the effects of light on motility, O2 consumption rate and CCO activity, but not to the same extent than that observed for antimycin A. Finally, the effects observed when sperm were co-incubated with antimycin A and PKCi were similar to those observed with antimycin A alone. In conclusion, red LED light acts on sperm function via a direct effect on mitochondrial electron chain. Additionally, light-activated PKC pathways have a supplementary effect to that observed in the electron chain, thereby modulating sperm parameters such as motility and CCO activity.